Slavery and Black Labour in a St. Mary’s Bay Acadian Family, 1786-1840 - Gaudet, Colby (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2023)
Documents left by a French Roman Catholic missionary and an Acadian merchant captain with Caribbean connections have revealed that Black people were enslaved by, and in other unfree and labouring relations with, a prominent Acadian network. Analyzed and placed into conversation with broader studies of Maritime slavery and the silences of Acadian public memory, these sources position two well-known Acadian community leaders alongside other Loyalist slaveholders in early Nova Scotia. The heirs of these two men signed an 1807 petition to the provincial legislature to secure their property in slaves at a time when anti-slavery sentiment and abolitionist policy were otherwise gaining influence in the British Empire.